Nanoscopic biodosimetry using plasmid DNA in radiotherapy with metallic nanoparticles. Issue 2 (22nd December 2022) - Mansouri, Elham; Mesbahi, Asghar; Hejazi, Mohammad Saied; Montazersaheb, Soheila; Tarhriz, Vahideh; Ghasemnejad, Tohid; Zarei, Mojtaba
Abstract: Nanoscopic lesions (complex damages), are the most lethal lesions for the cells. As nanoparticles have become increasingly popular in radiation therapy and the importance of analyzing nanoscopic dose enhancement has increased, a reliable tool for nanodosimetry has become indispensable. In this regard, the DNA plasmid is a widely used tool as a nanodosimetry probe in radiobiology and nano‐radiosensitization studies. This approach is helpful for unraveling the radiosensitization role of nanoparticles in terms of physical and physicochemical effects and for quantifying radiation‐induced biological damage. This review discusses the potential of using plasmid DNA assays for assessing the relative effects of nano‐radiosensitizers, which can provide a theoretical basis for the development of nanoscopic biodosimetry and nanoparticle‐based radiotherapy.